Biological and mechanical evaluation of poly(lactic-co-glycolic acid)-based composites reinforced with 1D, 2D and 3D carbon biomaterials for bone tissue regeneration. (20th March 2017) - Kaur, Tejinder; Kulanthaivel, Senthilguru; Thirugnanam, Arunachalam; Banerjee, Indranil; Pramanik, Krishna
Abstract: Considering the fact that life on Earth is carbon based, carbon materials are being introduced in biological systems. However, very limited information exists concerning the potential effects of different structures of carbon materials on biological systems. In the present study, poly(lactic-co-glycolic acid) (PLGA)-based carbonaceous composites were developed by reinforcing 1 wt% of three different carbon-based materials i.e. carbon nanotubes (CNTs-1D), graphene nanoplatelets (GNPs-2D), and activated carbon (AC-3D). The developed composites were characterized for physicochemical, biological, and mechanical properties. Along with their hemocompatible nature, the composites exhibited better swelling ratio, degradation percentage, bioactivity, and tensile strength. The improvement in hydrophilicity and protein adsorption resulted in the enhancement of cell proliferation and differentiation. Overall, sheet-like GNPs showed the strongest effect on the composite's properties due to their larger exposed area. These results demonstrate the potential of PLGA-based carbonaceous composites for accelerating bone tissue regeneration.